The Influence of E-Commerce Trust, Site Loyalty, and Satisfaction on Digital Consumer Purchase Behavior - Anora, Ayu; Muchayatin; Ginting, Yanti Mayasari (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The rapid growth of the e-commerce sector has transformed the way consumers interact with the market. Key factors influencing consumer purchase decisions on digital platforms include trust in the site, user loyalty, and customer satisfaction. This study aims to analyze the relationship between these three factors and consumer purchase behavior. Data were collected through a survey of 300 respondents with active online shopping experience, using a five-point Likert scale questionnaire. The analytical technique employed was Structural Equation Modeling (SEM) to examine the relationships between variables. The findings indicate that trust in digital platforms significantly influences purchase decisions, followed by customer satisfaction and site loyalty. Additionally, the impact of social media was found to strengthen consumer trust and loyalty, leading to repeat purchases. These findings highlight the importance of maintaining transparent and secure relationships with consumers, as well as providing a sufficient shopping experience to enhance satisfaction and loyalty. This study offers guidance for e-commerce managers in designing effective strategies to retain customers and encourage repeat transactions.